Changing Structure of Concessional Loan in Nepal - Gautam, Shyam Sunder (Journal of Interdisciplinary Studies, 2023)
This article highlights the changing scenario of concessional loan in Nepal. It examines the policies, trends, and structural shifts within the country’s financial framework. A concessional loan is a crucial tool for the economic development of Nepal. It aimed at promoting economic efficiency and equitable distribution of income throughout the country. Using secondary data from FY 2017/18 to FY 2021/22, this study evaluates the trend and structure of concessional loan in Nepal. The findings reveal that there is a significant surge in both the volume of concessional loan and the number of borrowers across different headings of concessional loan. Particularly, the number of borrowers of Women entrepreneurship loan are remarkably increased in the recent years. However, the concentration of loan among larger borrowers and the misappropriation of funds raises concerns regarding the program’s effectiveness. Furthermore, the commercial banks play a dominant role in disbursing concessional loan. Agricultural Development Bank Limited is a key contributor, aligning with the government’s focus on promoting the agricultural sector. This study recommended a call for a comprehensive evaluation of the concessional loan program. The reevaluation of the program could be crucial to fine-tune the policies, address challenges, and focus the program toward its goals of enhancing productivity, promoting financial inclusion, and fostering equal distribution income distribution in Nepal.